STANDARD TRAINING EXERCISES FOR HIGH SCHOOL STUDENTS - Tursunovich, Sodiqov Akbar; Abdumuratovich, Sultanov Bakhtiyor; Rustam, Egamberdiev; Siddikovich, Toychiev Sabir (International Journal of Psychosocial Rehabilitation, 2020)
The development of physical qualities in the classroom and extracurricular forms of instruction in general education schools to date is one of the least studied areas of exercise load regulation. Effective development of physical qualities is achieved only under the conditions of compliance with the norm of all parameters of load regulation. The development of students ’physical qualities is based on increasing their physical fitness through the regulation of exercises